1979
DOI: 10.1042/bj1840643
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-fibroblast interactions in collagenase production and cartilage degradation

Abstract: Rabbit bone-marrow macrophages and fibroblasts were cultured, independently or together, with pieces of 35S-labelled cartilage or at the surface of dried [14C]collagen gels. Each type of cell, cultivated alone, rapidly degraded the proteoglycan of cartilage, but only the fibroblasts degraded collagen. The co-culture of both types of cell had no consistent effect on the rate of proteoglycan degradation, but it stimulated the rate of collagen degradation. In parallel, the accumulation of collagenase in the cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

1981
1981
1985
1985

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 18 publications
1
27
0
1
Order By: Relevance
“…The present results with neutrophils, and our previous studies with lymphocytes (18,19) and macrophages (18), suggest a mechanism for modulation of heparanase activity and release in response to various signals. On the other hand, blood-borne tumor cells either may exhibit a constitutive expression of the enzyme in correlation with their metastatic potential (16,17) or can recruit normal cells (macrophages, neutrophils, lymphocytes, and platelets) and capitalize on their ability to infiltrate tissues (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…The present results with neutrophils, and our previous studies with lymphocytes (18,19) and macrophages (18), suggest a mechanism for modulation of heparanase activity and release in response to various signals. On the other hand, blood-borne tumor cells either may exhibit a constitutive expression of the enzyme in correlation with their metastatic potential (16,17) or can recruit normal cells (macrophages, neutrophils, lymphocytes, and platelets) and capitalize on their ability to infiltrate tissues (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…These authors showed that although matrix degradation took place in cultures of synovium over-lapping with dead cartilage, optimal proteoglyean release required interaction of living synovium with live cartilage. A related group of investigations have dealt with factors secreted by mononuclear cells that induce secretion of collagenase and neutral proteases from chondrocytes (7)(8)(9), rheumatoid synovial cells (10), fibroblasts (11), and macrophages (12) in culture. It was postulated that the increased production of these enzymes in vivo may mediate cartilage degradation, but there has been no direct evidence that connective tissue cells stimulated by such factors are able to mediate matrix degradation in living cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…Thus rabbit macrophage factor(s) or monokine(s) appear to be able to stimulate the release or the activity of several neutral proteases active in collagen and proteoglycan degradation by rabbit libroblasts [4,5], chondrocytes [15] or synovial cells [5]. Similarly, a human mononuclear cell factor has been shown to stimulate collagenase [ 161 or plasminogen activator [17] production by human synovial cells and a human synovial cell factor (possibly released by the macrophage-like, type-A synovial lining cells, as discussed in [3]) stimulates the activation of plasminogen by human chondrocytes [IS].…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage-conditioned media were obtained by culturing [4,7] adherent macrophages for 6 days at 37°C in plastic Petri dishes in basal medium supplemented with 10 mM-HEPES and 5% acidtreated FCS at a density of 5 x lo5 cells/ml (about 8 X 104 cells/cm2). The conditioned medium was then centrifuged and stored at -20°C until use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation